Architectural patterning in the Purepecha heartland: an intrasite settlement study at the urban center of Sacapu Angamuco, Michoacán, México - Bush, Jason W., author; Fisher, Christopher, advisor; Van Buren, Mary, committee member; Laituri, Melinda, committee member (Colorado State University. Libraries, 2012)
The overall goal of this thesis is to examine the architectural patterns of Sacapu Angamuco (Angamuco), a recently discovered Early-Middle Postclassic (A.D. 900-1350) urban settlement in the Lake Pátzcuaro Basin (LPB), Michoacán, Mexico that is located on an ancient lava flow, or malpais, and was extensively modified by prehispanic inhabitants to construct thousands of structures such as platforms, mounds, plazas, passages, stairs, and temples. Central to this thesis is how prehispanic residents of Angamuco organized their buildings and social space. The study of architectural remains is one critical component of ancient urbanism which is fundamental to Mesoamerican societies. Angamuco provides a rich opportunity to understand urbanism in the LPB. Understanding the spatial context of buildings and how they are grouped in functionally discernable ways is crucial to interpreting the internal function(s) of the settlement, as well as contributing to regional settlement pattern analyses. This thesis incorporates intensive survey using GPS, GIS, and remote sensing to document architecture and analyze the spatial patterns of architecture at Angamuco using data from the 2010 field season. An overview of relevant definitions and approaches to Mesoamerican urban settlement studies and the study of spatial patterning and classification of architecture is presented. A description of the physical setting of the LPB and Angamuco, the cultural-historical background of the region, and background information on previous archaeological work addressing urbanism, settlement patterns, and architecture in the LPB region is discussed. The research methodology used to collect data on Angamuco's architecture and settlement patterns is reviewed. The core of this work concerns an analysis of Angamuco architecture, beginning with description of the form and function of individual architectural features and analysis of architectural group form and patterning in the study area. Finally, the analysis is synthesized with the questions guiding this research, as well as current knowledge about Postclassic urbanism in the LPB and beyond. Ultimately, it is hoped that work at Angamuco will improve understanding of Postclassic LPB architecture, settlement patterns, and the role of cities before and during the development of the Tarascan Empire.
Keywords: Michoacan; Mexico; Mesoamerica